1987
DOI: 10.1128/aac.31.6.966
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of beta-lactamase-producing Haemophilus parainfluenzae from the genital tract

Abstract: Three Haemophilus parainfluenzae strains isolated from the urogenital tract harbored a beta-lactamase-coding 3.2-megadalton plasmid identical, by restriction endonuclease digestion and hybridization with radioactive and biotin-labeled probes specific for the TEM-1 beta-lactamase and TnA sequences, to the 3.2-megadalton "African-type" plasmid found in Neisseria gonorrhoeae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…After the recognition of plasmid-mediated beta-lactamase in gonococci, it was speculated that Haemophilus parainfluenzae may have been the plasmid source, or at least the host immediately prior to the gonococcus (180). Recently, we have seen what may be transfer in the other direction, with gonococcal-like plasmids reported in H. parainfluenzae (122).…”
Section: Legionella Sppmentioning
confidence: 99%
“…After the recognition of plasmid-mediated beta-lactamase in gonococci, it was speculated that Haemophilus parainfluenzae may have been the plasmid source, or at least the host immediately prior to the gonococcus (180). Recently, we have seen what may be transfer in the other direction, with gonococcal-like plasmids reported in H. parainfluenzae (122).…”
Section: Legionella Sppmentioning
confidence: 99%
“…The bacterium is notorious for β-lactamase production, and its β-lactamase producing ability is typically mediated by transferable plasmids. 17,[24][25][26] H. parainfluenzae is also considered as the origin and reservoir for the dissemination of β-lactamase-carrying plasmids to other bacterial species. 27 The β-lactamases detected include the TEM-1 and TEM-15 types, which are usually associated with plasmids.…”
Section: β-Lactam Antibioticsmentioning
confidence: 99%
“…14,16,28,29 It was reported that the plasmid that carried the TEM-1 β-lactamase was identical to one isolated from 'Africantype' penicillinase-producing Neisseria gonorrhoeae strain. 26,30 Inhibitor resistant β-lactamases TEM-34 and TEM-182, which were both carried by TnA transposon of the Tn2 type, were also detected in H. parainfluenzae in 2011. 16 β-lactam resistance in H. parainfluenzae not mediated by β-lactamases has also been reported.…”
Section: β-Lactam Antibioticsmentioning
confidence: 99%
“…They can be mobilized by the 24.5-megadalton (MDa) indigenous conjugative gonococcal plasmid, conjugative Haemophilus plasmids, and enteric plasmids (9,10,14,15,19). The 3.2-MDa 3-lactamase plasmid has also been associated with strains of Haemophilus ducreyi and urogenital Haemophilus parainfluenzae (1,13). In contrast, the ,-lactamase plasmid was maintained in only a few strains of Neisseriaflava, Neisseria cinerea, Neisseria subflava, Neisseria mucosa, and N. subflava-N. sicca but not in strains of Neisseria meningitidis under laboratory conditions (8).…”
mentioning
confidence: 99%